Immuno-histochemical analysis of rod and cone reaction to RPE65 deficiency in the inferior and superior canine retina - Klein, Daniela; Mendes-Madeira, Alexandra; Schlegel, Patrice; Rolling, Fabienne; Lorenz, Birgit; Haverkamp, Silke; Stieger, Knut; Justus Liebig University Giessen (My University, 2014)
Mutations in the RPE65 gene are associated with autosomal recessive early onset severe retinal dystrophy. Morphological and functional studies indicate early and dramatic loss of rod photoreceptors and early loss of S-cone function, while L and M cones remain initially functional. The Swedish Briard dog is a naturally occurring animal model for this disease. Detailed information about rod and cone reaction to RPE65 deficiency in this model with regard to their location within the retina remains limited. The aim of this study was to analyze morphological parameters of cone and rod viability in young adult RPE65 deficient dogs in different parts of the retina in order to shed light on local disparities in this disease. In retinae of affected dogs, sprouting of rod bipolar cell dendrites and horizontal cell processes was dramatically increased in the inferior peripheral part of affected retinae, while central inferior and both superior parts did not display significantly increased sprouting. This observation was correlated with photoreceptor cell layer thickness. Interestingly, while L/M cone opsin expression was uniformly reduced both in the superior and inferior part of the retina, S-cone opsin expression loss was less severe in the inferior part of the retina. In summary, in retinae of young adult RPE65 deficient dogs, the degree of rod bipolar and horizontal cell sprouting as well as of S-cone opsin expression depends on the location. As the human retinal pigment epithelium (RPE) is pigmented similar to the RPE in the inferior part of the canine retina, and the kinetics of photoreceptor degeneration in humans seems to be similar to what has been observed in the inferior peripheral retina in dogs, this area should be studied in future gene therapy experiments in this model.
Keywords: ddc:610